Videnskabelig oversættelse af den hebraiske bibel - Herbener, J.A. (Nordisk judaistik/Scandinavian Jewish Studies, 2001)
In this report, the author discusses the translation process of the Hebrew bible into Danish. The author makes a distinction between a confessional translation process, where the experts involved are mainly theologians, and a scientific translation process, where the experts are philologists in Semitic languages. When translations of the bible are conducted on a confessional basis, the result is highly dependent on the Christian or Jewish background of the interpreter.